2017
DOI: 10.1002/ptr.5982
|View full text |Cite
|
Sign up to set email alerts
|

6‐shogaol induces apoptosis and enhances radiosensitivity in head and neck squamous cell carcinoma cell lines

Abstract: Ginger (Zingiber officinale Roscoe) is used for a wide array of conditions in traditional medicine in Asia, but little is known about the effect on head and neck cancer. In this study, the effect of two major pharmacologically active compounds of ginger, 6-gingerol and 6-shogaol, were studied on head and neck cancer cell lines. Furthermore, experiments in combination with established treatment methods for head and neck cancer were performed. Proliferation assays showed a dose-dependent reduction of cell viabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 42 publications
0
14
1
1
Order By: Relevance
“…Statistical analysis was performed using a Student's unpaired t-test or a Kruskal-Wallis nonparametric analysis of variance (ANOVA) with Dunn's post hoc test, and results were considered statistically significant when P<0.05 or P<0.01. (18)(19)(20). However, in this study, we found that low doses of GPE (0.001-0.1 µg/ml) had a minimal effect on cell viability.…”
Section: Wound Healing Assay (Cell Migration)contrasting
confidence: 60%
See 1 more Smart Citation
“…Statistical analysis was performed using a Student's unpaired t-test or a Kruskal-Wallis nonparametric analysis of variance (ANOVA) with Dunn's post hoc test, and results were considered statistically significant when P<0.05 or P<0.01. (18)(19)(20). However, in this study, we found that low doses of GPE (0.001-0.1 µg/ml) had a minimal effect on cell viability.…”
Section: Wound Healing Assay (Cell Migration)contrasting
confidence: 60%
“…Treatment with GPE (~0.1 µg/ml) did not affect cell viability, indicating that GPE (~0.1 µg/ml) is nontoxic to mouse fibroblast cells, in contrast to several reports showing that the ingredients of ginger extracts, such as gingerol and shogaol, have cytotoxic activity (18)(19)(20). The discrepancy in the findings regarding the cytotoxic activity of ginger might be attributable to the difference in the doses of GPE used.…”
Section: Discussionmentioning
confidence: 63%
“…Ginger (binominal name: Zingiber officinale ) is a flowering plant originated in the tropical lowland forests in southern Asia and the Indian subcontinent (Adhikari, Indira Priyadarsini, & Mukherjee, ; Kotowski et al, ). Generally, ginger roots (rhizomes) are widely used as a food spice (Eliopoulos, ).…”
Section: Introductionmentioning
confidence: 99%
“…The potentiality of 6-shogaol is supported by several lines of evidence as an agent for the prevention and treatment of a variety of cancers including gastrointestinal, melanoma, breast, lung, head and neck [13,14,15,16,17]. Also, various in vitro and in vivo studies showed that 6-shogaol demonstrates more potent anti-inflammatory activity than 6-gingerol and another widely studied phytochemical, curcumin [18].…”
Section: Introductionmentioning
confidence: 99%